Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijms20215505
|View full text |Cite
|
Sign up to set email alerts
|

Biological Features Implies Potential Use of Autologous Adipose-Derived Stem/Progenitor Cells in Wound Repair and Regenerations for the Patients with Lipodystrophy

Abstract: A paradigm shift in plastic and reconstructive surgery is brought about the usage of cell-based therapies for wound healing and regeneration. Considering the imitations in the reconstructive surgeries in restoring tissue loss and deficiency, stem cell-based therapy, in particular, has been expected to pave the way for a new solution to the regenerative approaches. Limitations in the reconstructive surgeries in restoring tissue loss and deficiency have paved the way for new regenerative approaches. Among them, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
(64 reference statements)
1
12
0
Order By: Relevance
“…Although the approved treatments for PAH have been improved, clinical prognosis of patients remain poor [28]. Accumulating studies have documented that ADSCs were originated from stromal-vascular fragments of adipose tissue and used for therapeutic application due to its pluripotent differentiation and immune tolerance [6,10]. In the present study, we observed that exosomes from ADSCs was able to improve hypoxia-induced PAH by regulating endothelial cells disorders and in ammation response.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Although the approved treatments for PAH have been improved, clinical prognosis of patients remain poor [28]. Accumulating studies have documented that ADSCs were originated from stromal-vascular fragments of adipose tissue and used for therapeutic application due to its pluripotent differentiation and immune tolerance [6,10]. In the present study, we observed that exosomes from ADSCs was able to improve hypoxia-induced PAH by regulating endothelial cells disorders and in ammation response.…”
Section: Discussionsupporting
confidence: 52%
“…Enormous attention has been focusing on the ADSCs due to the easy isolating procedure and a higher harvest rate than bone marrow [8,9]. Increasing evidence have shown that ADSCs has been proven to be useful for corneal wounds and regenerating non-healing cutaneous, cardiovascular disease [10,11]. Exosomes (exos) are vesicles with a size of 30-200 nm derived from the cell membrane of cells and released to the extracellular environment after fusion of multivesicular endosomes and plasma membranes under normal or pathological conditions [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Adipogenic differentiation is an important direction of MSCs differentiation which has attracted much attention in recent years. Adipogenic differentiation plays an important role in the regeneration of damaged organs and the repair of adipose tissue ( Zhao et al, 2017 ; Morissette Martin et al, 2018 ; Suzuki et al, 2019 ). Studies demonstrate that microRNAs and glucocorticoids are related with adipogenic differentiation ( Han et al, 2019 ; Lorente-Cebrian et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, adverse events may occur due to the collection of ectopic fat tissue for use as donor cells, and it is not always possible to obtain sufficient autologous fat tissue safely to achieve good functional and cosmetic results. Patients with fat tissue atrophy may also show symptoms due to lack or reduction of adipocyte functions such as energy storage, cushioning of organs and thermoregulation, as well as endocrine and secretory functions [ 5 , 6 ]. Adipokines secreted from adipocytes play crucial roles in physiological responses, such as metabolic homeostasis, angiogenesis, and inflammatory and immune regulation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%